Editorial: monitoring blood pressure is key to the safe use of beta‐blockers in patients with chronic liver failure. Issue 2 (19th December 2017) - Ferguson, J. W.; Armstrong, M. J.
Abstract : Linked Content This article is linked to Bhutta et al paper. To view this article visithttps://doi.org/10.1111/apt.14366 .